Registro da atuação do movimento dos atingidos por barragens nos reassentamentos de Acauã: a alfabetização de jovens e adultos - Medeiros, Edileuza Custodio Rodrigues de (2010)
This work contains the problematic of sub-education among the population that was excluded from school attendance in the regular time, contributing to knowledge production about educational practices developed in EJA (the Young and Adult Education). It focuses on the Pedagogical proposal and on the experience in young and adult literacy in the context of the mobilization of people affected by dam building. It depicts the international, national and regional mobilization against huge dams building and the emergence of the Movement of Dam Affected People (MAB), highlighting their general project and registering their teaching performance, particularly in young and adult literacy. In methodological and theoretical approaches, two interconnected categories are considered: the historical entirety, essentially theoretical, and the young and adult education practice. Based on the entirety, it outlines a contextualized explanation about the stakeholder s situation and, respecting the second category, which is part of the first one, places literacy as one of the basic aspects of an omnilateral man upbringing. The study broaches a wide context of dams in the world, placing the socio-environmental effects resulting from dams building in Brazil, in Northeast region and in Paraíba, and emphasizing the consequences of Acauã Dam building in the Paraíba cities of Aroeiras, Itatuba and Natuba. It presents the particular context of the population affected by Acauã, summarizing a panoramic view about the involved Paraíba cities and learning the conditions of residents relocation. It appraises the educational project and the National-MAB literacy proposal, operationalized by Paraíba-MAB in resettlements sited on Acauã s surroundings. It ensures that, besides public policies including financing, the feasibility of literacy problem solution can be completed with Pedagogical actions attached to the target people peculiarities and immediate necessities, respecting actions connected through one comprehensive and contextualized educational project. It evaluates the young and adult literacy project developed in the restricted Paraíba-MAB area, as an example of a Pedagogical action minimally contextualized. Eventually, it recommends researchers and teachers in general, that are committed to this work perspective, to pay attention to the way they articulate discussions and participation, so as to contemplate these communities expectations and necessities in Pedagogical projects and spaces based on discussion, dialogue and collective reflection